Efficacy of Antimicrobial-Impregnated Catheters for Prevention of Bloodstream Infections in Pediatric Patients: A Meta-Analysis - Lai, Li; Yue, Xuan (Frontiers in Pediatrics, 2021)
Background: Multiple Randomized controlled trials (RCTs) have evaluated the efficacy of antimicrobial-impregnated catheters to prevent catheter-related bloodstream infections (CRBSI). However, the RCTs showed contradictory results, the studies were limited in sample size and methodology quality. Thus, we conducted a meta-analysis to overcome these RCT limitations. Methods: We designed a meta-analysis of RCTs comparing antimicrobial-impregnated and conventional catheters for the prevention of CRBSI. We conducted a detailed search of various databases for RCTs published before November 2019. We calculated mean differences (MDs) and pooled odds ratios (ORs) with 95% confidence intervals (CIs) using a random-effects model. Results: We included five RCTs with a total of 2,294 patients. The incidence of CRBSI between the two groups was 0.50 (95% CI, 0.19–1.27), with evidence of heterogeneity (I2 = 55%). The difference was not statistically significant (p = 0.15). On subgroup analysis based on the age of the sample, there was no difference in the rate of CRBSI in the neonatal population [0.42 (95% CI, 0.08–2.27 I2 = 61% p = 0.31] as well as pediatric population [0.45 (95% CI, 0.12–1.67 I2 = 39% p = 0.23]. The summary OR on the incidence of catheter colonization between antimicrobial-impregnated and conventional catheters was 0.64 (95% CI, 0.17–2.35), with no evidence of heterogeneity (I2 = 0%) and a non-significant difference (p = 0.50). Conclusions: To conclude, analysis of a limited number of heterogeneous studies mostly with a small sample indicates that the CRBSI and catheter colonization rates are similar between conventional and antimicrobial-impregnated catheters in the pediatric and neonatal population. There is an urgent need for large-scale RCTs focusing on different antimicrobial-impregnated catheters in these patients to further enhance current evidence.